MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK USIA 4-5 TAHUN MELALUI BERMAIN BALOK DI KOBER BANI YAHYA - Nur, Maulida; Abqoriah, Abqoriah; Pahrul, Yolanda; Rini, Ratu Yustika; Mulyawan , Galuh (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
This study aims to enhance the cognitive abilities of children aged 4–5 years through block play activities at Kober Bani Yahya in Serang City, Banten. The background of the study emphasizes the importance of the play-and-learn approach in early childhood development. The research adopted a two-cycle Classroom Action Research design involving 10 children in Group A. Each cycle comprised four stages: planning, implementation, observation, and reflection. Data were collected through observations, interviews, and documentation, and analyzed using both qualitative and quantitative methods. The results indicated a significant improvement in the children’s cognitive abilities. In the pre-cycle, the average cognitive ability ranged from 35–40% (Undeveloped category). Following the block play intervention, the average increased to 58–65% (Starting to Develop and Developing as Expected categories) in Cycle I. The highest improvement was recorded in Cycle II, where the average reached 83–90%, with most children categorized as Very Well Developed.These findings confirm that block play effectively enhances cognitive skills such as shape and size classification, color recognition, problem-solving, and symbolic reasoning. The study concludes that block-based learning is a concrete, enjoyable, and relevant approach to optimizing early childhood cognitive development